Marketing strategy of Nike - Ismailova, Mariam; Průša, Přemysl, 1980-; Asmalovskij, Alexandr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2019)
Founded in 1976, Nike became a global leader in the footwear market in 2019. This thesis aims to present the marketing strategy of Nike. In the theoretical part, I described the brief history, marketing strategy and objectives of Nike. To answer, how Nike got strong positioning in the market, in the practical part, there is a critical assessment of the current marketing strategy of Nike and the revelation of the main critical success factors as well as suggestions of some proposals for further improvement. This thesis analyses segmentation, targeting, positioning of the Nike and marketing/communication mixes of the company.In this thesis are presented the Czech target market, SWOT analysis of the Nike and research among potential customers of the Nike SB collection – skaters segment.Results showed a trivial effect on the Czech market by Nike’s promotion, but globally it is keeping first positions with the biggest advertising budget and wide range of the product or service offerings.This study emphasizes to handle Nike’s global weakness and opportunities by a company, so there are recommendations included.
Vedoucí práce: Přemysl Průša
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses